BK Teachers' Efforts to Prepare Grade XII Students to Decide on Advanced Education - Rizky Habibi Matondang; Khairuddin Tambusai (MASI Mandiri Edukasi, 2025)
The number of students in grade XII of Budisatrya Private High School amounted to 154 people, 43% of students continued to higher education, and 57% did not continue to college. They choose to try to apply for jobs, for example, to become members of the Police, TNI, Security Guards, entrepreneurs, and factory workers. Guidance and counselling teachers help grade XII students for further education by directing and motivating them to continue their college education. Counseling guidance teachers give students views on the importance of education, how the university is portrayed, provide the latest information about the university, prospective police or army applications and job vacancy information for high school graduates and advise that a bright future cannot be achieved without hard work, therefore students are expected to always strive to achieve their goals with optimism and persistence. The supporting factors of counselling guidance teachers in preparing students for further education are the existence of lively socialisation between the school and the university and socialisation between the school and alumni that make it easier for students to continue to college, careers, entrepreneurship, and factory workers. Factors that hinder guidance and counselling teachers in preparing students for further education are the absence of transfer from university to school, and the lack of socialisation time, so socialisation runs less than optimally.